On the Limits of Empirical Ecocriticism : Empathy on Non-Human Species and the Slow Violence of Climate Crisis - Lahtinen, Toni; Löytty, Olli (Taylor & Francis, 2025)
The impact literature has on its readers has recently become a topic of interest to an increasing number of literary scholars who contemplate the relationships between environment and fiction. Empirical ecocriticism is a relatively young sub-area of ecocriticism where the empirical methods of social sciences are applied. This article discusses two major areas in empirical ecocriticism: the emotions evoked by both the representations of non-human species and climate literature. The focus is not solely on the premises of empirical ecocriticism but also on the often-conflicting results it has produced. By presenting critical observations on its limits so far, the article proposes outlines for further development of empirical research on environmental fiction.